OP0085 Infliximab plus methotrexate improves signs and symptoms in initial non-responders who continue treatment. (1st June 2001) - Keystone, E; Patel, K; Keenan, G; Schaible, T
Abstract : Background: In an international, placebo-controlled, randomised trial, 428 patients with active RA despite methotrexate (MTX) therapy received placebo (i.e. MTX alone) or infliximab at 3 mg/kg or 10 mg/kg every 4 or 8 weeks along with MTX for 102 weeks. In this trial, infliximab plus MTX improved signs and symptoms, inhibited progression of structural damage, and improved physical function compared to MTX alone. Objectives: To determine if continued treatment with infliximab benefits patients who are not ACR20 responders at week 30. Methods: Patients who were not responders according to ACR20 criteria at week 30 were identified. Their clinical response to continued treatment was assessed based on ACR-N at the week 54 and week 102 visits. Analysis of variance on the van der Waerden normal scores was used to compare the ACR-N values at these time points. Radiologic response is based on the modified total Sharp score (TSS). Results: The ACR-N and change in TSS at weeks 30, 54 and 102 are shown in the Table 1 . The ACR-N was higher in the infliximab treated groups, compared to the placebo treated group at weeks 54 and 102. The change in TSS was higher at all time points in the placebo group as compared to the infliximab treated groups. Conclusion: Patients who did not initially benefit from infliximab treatment derived clinical benefit when they continued to be treated long-term. Radiographic benefit was noted over time in all of the infliximab treated groups. The time point at which patients can be categorised as clinical non-responders to infliximab therapy needs further examination.